Factores que influyen en la depresión en internos de enfermería del hospital básico de playas, 2023” - Barrera Landa, Jeremy Alexis (2024)
The nursing interns, students in pre-professional internships, face various emotional challenges, which can lead to depression. The high demand and work responsibility, along with intense schedules and demanding tasks, increase the risk of developing depressive symptoms. The lack of time for self-care and constant contact with patients' suffering also contribute to this vulnerability. The accumulation of traumatic experiences can trigger depressive episodes in these students. The objective was to identify, through surveys, the factors influencing depression in nursing interns at Playas Basic Hospital, 2023. The research approach is quantitative, with a descriptive correlational scope, non-experimental. To obtain results on the factors that generate depression in nursing students, a survey with a questionnaire of questions was conducted, which was applied virtually. The results revealed that 68% of the respondents were female, while 32% were male. Regarding the age of the participants, 34% were 22 years old, 24% were 23 years old, 26% were 24 years old, and 16% were in the age range between 25 and 29 years old. Regarding the relationship between support received at work and the presence of depressive symptoms, 75% of respondents claimed to receive adequate support from their superiors and colleagues, while 20% claimed to receive it often, and only 5% claimed to receive it rarely. On the other hand, regarding participation in institutional activities as a coping strategy, 50% of respondents claimed to always participate, 25% often, 17% rarely, and 8% never participated in these activities